2004
DOI: 10.1159/000081004
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Inhibitor, Argatroban, Prevents Tumor Cell Migration and Bone Metastasis

Abstract: It is well known that malignant cells show procoagulant activity, which is associated with their metastatic potential. Thrombin, the key enzyme of the blood coagulation system, is generated around tumor cells, promoting the migration and metastasis of tumor cells. In this study, we evaluated the effect of argatroban, a specific thrombin inhibitor, on the migration and metastasis of B16BL6 melanoma cells. In vitro argatroban dose-dependently inhibited cell migration, the maximum inhibition being observed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 69 publications
2
40
0
Order By: Relevance
“…Argatroban was used at concentrations of 25 lg/ml (*50 lM) for all in vitro assays (cell growth, colony-forming ability, apoptosis, adhesion, migration) and 9 mg/kg/day for all in vivo animal studies. These doses were chosen based on previous studies by Asanuma et al [10] that demonstrated maximal inhibition of in vitro B16 mouse melanoma cell migration in the range of 10-100 lM, and inhibition of bone metastasis in vivo using a dose of 9 mg/kg/day [10].…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Argatroban was used at concentrations of 25 lg/ml (*50 lM) for all in vitro assays (cell growth, colony-forming ability, apoptosis, adhesion, migration) and 9 mg/kg/day for all in vivo animal studies. These doses were chosen based on previous studies by Asanuma et al [10] that demonstrated maximal inhibition of in vitro B16 mouse melanoma cell migration in the range of 10-100 lM, and inhibition of bone metastasis in vivo using a dose of 9 mg/kg/day [10].…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
“…Argatroban (9 mg/kg/day; treated groups) or saline (untreated groups) was administered subcutaneously starting 10 days after tumor cell injection for the duration of the experiment. This dose regimen was chosen based on a previous study which demonstrated an effect on experimental metastasis of B16F10 mouse melanoma following intracardiac cell injection [10]. Primary tumor growth was evaluated weekly by caliper measurement in two perpendicular dimensions, and tumor volume was estimated using the following formula: [volume = 0.52 9 (width) 2 9 (length)] for approximating the volume (mm 3 ) of an ellipsoid.…”
Section: Cell Migration Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignancy is an abnormal manifestation of tissue repair activity that occurs when prolonged and exaggerated positive feedback causes SRM repair hyperactivity to become selfsustaining [204,210,593]. Malignant cells invade normal tissues, release tissue factor, activate nervous sensors, and cause a "vicious cycle" of positive feedback that sustains abnormal thrombin elevations that inhibit the apoptosis and resolution that normally occurs at the conclusion of the tissue repair process [29,82,216,217,[594][595][596][597]. For example, uncontrolled osteomyelitis sometimes evolves into osteosarcoma.…”
Section: Inflammation Apoptosis and Malignancymentioning
confidence: 99%
“…Similarly, argatroban attenuates metastasis in melanomas. 8 These effects are dose-dependent. Interestingly, argatroban also attenuates ischemia/ reperfusion-induced liver metastasis from colon carcinomas.…”
mentioning
confidence: 99%